2016
DOI: 10.1038/nchembio.2179
|View full text |Cite
|
Sign up to set email alerts
|

A chemical-inducible CRISPR–Cas9 system for rapid control of genome editing

Abstract: CRISPR-Cas9 has emerged as a powerful technology that enables ready modification of the mammalian genome. The ability to modulate Cas9 activity can reduce off-target cleavage and facilitate precise genome engineering. Here we report the development of a Cas9 variant whose activity can be switched on and off in human cells with 4-hydroxytamoxifen (4-HT) by fusing the Cas9 enzyme with the hormone-binding domain of the estrogen receptor (ERT2). The final optimized variant, termed iCas, showed low endonuclease act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
170
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(178 citation statements)
references
References 35 publications
4
170
0
Order By: Relevance
“…On the other hand, lessening the promiscuity of SpCas9 can be achieved by lowering its activity on off-target sequences while maintaining reasonably effective on-target activities. This is attempted by minimizing the exposure of the DNA to SpCas9 activity by limiting the time of its expression [24,25,[54][55][56][57] or decreasing the level of protein [58,59], employing modified sgRNAs (truncated [23] or 5′ extended with a GG dinucleotide [21]) or weakening the protein-DNA interactions [32,33]. Although a systematic comparison of these approaches is still missing, they have led to varying success and it has been observed that different targets are cleaved with different off-target propensity by SpCas9.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lessening the promiscuity of SpCas9 can be achieved by lowering its activity on off-target sequences while maintaining reasonably effective on-target activities. This is attempted by minimizing the exposure of the DNA to SpCas9 activity by limiting the time of its expression [24,25,[54][55][56][57] or decreasing the level of protein [58,59], employing modified sgRNAs (truncated [23] or 5′ extended with a GG dinucleotide [21]) or weakening the protein-DNA interactions [32,33]. Although a systematic comparison of these approaches is still missing, they have led to varying success and it has been observed that different targets are cleaved with different off-target propensity by SpCas9.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation at the transcriptional level, however, offers poor temporal control compared with post-transcriptional and post-translational control, and is difficult to achieve in many cell types due to a lack of tissue-specific promoters. Post-translationally regulated Cas9 variants have been developed in which conditionally inactive Cas9 proteins are expressed and genome editing activity is restored only in the presence of specific stimuli12131415. Controlling the activity of Cas9 to limit the temporal exposure of cells to genome editing activity has resulted in important benefits such as reduced modification of off-target loci13.…”
mentioning
confidence: 99%
“…To limit Lama1 expression only to skeletal muscles, the promoter of deSaCas9-VP160 should be muscle specific. Moreover, to prevent overexpression of Lama1, the Cas9-VP64 gene or the sequences coding for the sgRNAs can be placed under a promoter inducible by doxycycline and 4-hydroxytamoxifen 41, 42, 43, 44…”
Section: Discussionmentioning
confidence: 99%